Mentoring: The Factors that Contribute to Persistence to Graduation for African American Male K-12 Educators in Predominantly White Institutions (PWI) in Missouri - Paula Miller (Adult Education Research Conference, 2024)
This study investigated how mentoring enabled African American male K-12 educators to persist and obtain master’s degrees in predominately White institutions (PWIs) in Missouri.
Keywords: mentoring; persistence; African American males